Беларуска-літоўскія калькi - Цыхун, Генадзь (Slavistica Vilnensis, 2009)
The article discusses the identification criteria of the Веlarusіаn-Lіthuаnіаn calques and the problem of the geographical distribution of the Ваltіс lехісаl borrowings and calques within the Belarusian linguistic territory.